2021
DOI: 10.3389/fonc.2021.687430
|View full text |Cite
|
Sign up to set email alerts
|

CD38 Multi-Functionality in Oral Squamous Cell Carcinoma: Prognostic Implications, Immune Balance, and Immune Checkpoint

Abstract: BackgroundCD38 belongs to the ribosyl cyclase family and is expressed on various hematological cells and involved in immunosuppression and tumor promotion. Although targeting CD38 antibodies has been approved for treatment of multiple myeloma, the function of CD38 in solid tumor, oral squamous cell carcinoma (OSCC) etc., has not been investigated.MethodsThis retrospective study included 92 OSCC samples and analyzed the spatial distribution of CD38 by immunohistochemistry (IHC). The values of diagnosis and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In HCC, a high frequency of CD38+PD-1+CD8+ T cells is associated with high histopathological grades (III and IV), thereby indicating that CD38, a T-cell co-exhaustion marker, is linked to tumor aggressiveness (27). A recent study has revealed that a heightened level of CD38 expression in TILs promotes increases in the levels of Ki-67 in tumor cells, and that highly expressed CD38+ TILs independently predict shorter OS and PFS (47). The findings of further studies have indicated that the progression of prostate cancer is associated with increases in CD38+ tumor-infiltrating immune cell density, which is independently associated with a worse OS (48).…”
Section: Discussionmentioning
confidence: 99%
“…In HCC, a high frequency of CD38+PD-1+CD8+ T cells is associated with high histopathological grades (III and IV), thereby indicating that CD38, a T-cell co-exhaustion marker, is linked to tumor aggressiveness (27). A recent study has revealed that a heightened level of CD38 expression in TILs promotes increases in the levels of Ki-67 in tumor cells, and that highly expressed CD38+ TILs independently predict shorter OS and PFS (47). The findings of further studies have indicated that the progression of prostate cancer is associated with increases in CD38+ tumor-infiltrating immune cell density, which is independently associated with a worse OS (48).…”
Section: Discussionmentioning
confidence: 99%
“…We also used bioinformatic analysis to confirm our results. Since OSCC is the most common type of epithelial malignant tumor in the head and neck, using the HNSCC cases in TCGA database for OSCC study is frequently applied by researchers [ 17 , 33 ]. In this study, by using the HNSCC cases in TCGA database, we found significant increases of PLOD2 mRNA levels in tumor tissues compared with normal tissues ( Figure 2 ), and highly expressed PLOD2 was associated with poor OS and DFS ( Figure 5 i,j).…”
Section: Discussionmentioning
confidence: 99%